2023
DOI: 10.3390/plants12040812
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Landraces’ Seed Health in South Italy and New Evidence on Crop Diseases

Abstract: During the last three years, more than 300 landraces belonging to different plant species have been the main focus of an Italian valorization research project (AgroBiodiversità Campana, ABC) aiming at analyzing, recovering, preserving, and collecting local biodiversity. In this context, phytosanitary investigation plays a key role in identifying potential threats to the preservation of healthy seeds in gene banks and the successful cultivation of landraces. The surveillance carried out in this study, in additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…In fact, Nicholson and coworkers demonstrated that seeds affected by S. sclerotiorum were flatter, smaller, and discolored, with decreased germination relative to healthy ones [ 118 ]. Seedborne infection with S. sclerotiorum was also observed in faba bean in Italy in 2022; the experimental infection of plants showed severe symptoms, ranging from leaf chlorosis to stem rot ( Figure 9 ) [ 119 ].…”
Section: Seedborne Fungi and Oomycetes Of Principal Leguminous Cropsmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, Nicholson and coworkers demonstrated that seeds affected by S. sclerotiorum were flatter, smaller, and discolored, with decreased germination relative to healthy ones [ 118 ]. Seedborne infection with S. sclerotiorum was also observed in faba bean in Italy in 2022; the experimental infection of plants showed severe symptoms, ranging from leaf chlorosis to stem rot ( Figure 9 ) [ 119 ].…”
Section: Seedborne Fungi and Oomycetes Of Principal Leguminous Cropsmentioning
confidence: 99%
“…When inoculated on grown plants, they were able to produce necrotic lesions that worsened over several days [ 17 ]. Similarly, Apiospora arundinis was isolated from the seeds of common bean, and, when inoculated into plants, typical necrotic spots on the leaves confirmed its pathogenicity in the new host [ 119 ]. Moreover, pathogenic Sclerotinia sclerotiorum was isolated for the first time from the seeds of faba bean and was shown to be able to induce leaf chlorosis and severe stem rot when artificially inoculated [ 119 ].…”
Section: New Reports In Leguminous Cropsmentioning
confidence: 99%
See 2 more Smart Citations